World Demographic Trends 2018 - United Nations (United Nations, 2019)
The present report, prepared in accordance with resolution 1996/2 of the ECOSOC, provides an overview of demographic trends for the world, its geographic regions and selected countries, and for various development and income groups. It focuses on major demographic changes during recent decades, as well as projected changes during the time frame for implementing the 2030 Agenda for Sustainable Development and beyond. The report includes population size and change, fertility and family planning, mortality, changing population age structures, urbanization and city growth, and international migration, including recent trends in the number of refugees and asylum seekers.